Beyond the blackboard: reimagining math education through flipped classrooms, AR, and GeoGebra - Prahesti Tirta Safitri; Kus Andini Purbaningrum (Sekolah Pascasarjana Universitas Muhammadiyah Prof. DR. Hamka bekerjasama dengan Himpunan Evaluasi Pendidikan Indonesia (HEPI)., 2025)
Purpose: To systematically investigate the learning outcomes of integrating flipped learning with Augmented Reality (AR) and GeoGebra in mathematics education, specifically addressing complex spatial geometry challenges where traditional success rates hover at 21%. Method: Guided by the PRISMA 2020 framework, this systematic literature review analyzed empirical data from the Scopus database. From an initial 67 records, 8 high-quality full-text articles published between 2020 and 2024 were selected. The studies encompassed diverse global contexts (Luxembourg, Indonesia, Spain, Vietnam) with participant cohorts ranging from 30 to 442 students, evaluated through narrative synthesis. Findings: The integrated approach significantly elevated student academic performance and problem-solving capabilities, yielding substantial effect sizes between 0.64 and 1.40. Key metrics include a 24.8% performance increase , score elevations from 11 to 17 on a 20-point scale , and a remarkable transformation from a 50% failure rate to a 100% pass rate , coupled with 97.3% student satisfaction. Practical Implications: Educators are provided with a validated three-phase pedagogical model: pre-class GeoGebra engagement, in-class AR collaborative problem-solving, and post-class authentic assessment, alongside a mandate for robust technological infrastructure. Originality/value: This review synthesizes a novel framework uniting three converging educational technologies, validating the TPACK framework within post-pandemic hybrid mathematics education.